2011
DOI: 10.1111/j.1445-2197.2011.05710.x
|View full text |Cite
|
Sign up to set email alerts
|

Using bilateral iliac branch devices for endovascular iliac aneurysm repair

Abstract: Bilateral IBDs can be used safely and with excellent rates of technical success and branch patency in appropriately selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…This assertion comes from balancing the results against previous large reports of unilateral IBDs, 2 as no disadvantage compared with unilateral use is presented in this work. Also, by comparison with other previous reports on bilateral IBD deployment, 3,4 which share common limitations of sample size and length of follow up, the procedure does not seem to be device dependent. However, the key point in this affair is whether the use of two IBDs in the same patient is justified and offers benefits over preserving just one hypogastric artery.…”
mentioning
confidence: 61%
“…This assertion comes from balancing the results against previous large reports of unilateral IBDs, 2 as no disadvantage compared with unilateral use is presented in this work. Also, by comparison with other previous reports on bilateral IBD deployment, 3,4 which share common limitations of sample size and length of follow up, the procedure does not seem to be device dependent. However, the key point in this affair is whether the use of two IBDs in the same patient is justified and offers benefits over preserving just one hypogastric artery.…”
mentioning
confidence: 61%
“…Huilgol et al [7] reported using bilateral iliac branch devices for endovascular iliac aneurysm repair. However, there is a lack of experimental data concerning the use of bilateral iliac branch devices, but their benefit can be inferred from what is known about the benefits of IIA preservation and the adverse outcomes of IIA occlusions.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one reported case of a deployed covered self-expanding stent preserving the IMA is available [7]. Maldonado et al [9] reported that 5 of 7 patients with pelvic ischemia had patent IMA before EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the presence or absence of symptoms highly depends on the pre-existing collateral circulation of the external iliac artery, profunda femoris arteries, mesenteric arcades and contralateral hypogastric artery. 16 It is also important to emphasize that patients with vascular disease and aneurysm formation, often simultaneously present with chronic embolization from mural thrombus of the aneurysm and/or concomitant atherosclerotic processes within the pelvic arteries. This may impair collateral branch irrigation, even if those branches do exist, making it difficult to predict which patients are more likely to develop complications and to what extent, solely based on the image study of the collateral circulation.…”
Section: Evidence Synthesis Deliberate Hypogastric Artery Occlusionmentioning
confidence: 99%
“…All in all, there are several techniques to be considered when treating aortoiliac aneurysms, and several factors should be measured upon the choice of the best treatment option. As pointed by Huilgol et al, 16 factors such as patient's life expectancy, their level of physical and sexual activity and the expected risk of serious ischemic complications from IIA embolization, should be assessed when choosing a treatment technique. Specific aneurysm morphology, the risks of a potentially longer procedure and associated larger contrast volumes, as well as the financial cost of the procedure and the endovascular skills required, should also be considered.…”
Section: C) Parallel-graftsmentioning
confidence: 99%